PENGEMBANGAN LKPD IPA BERBASIS PEDAGOGY FOR SUSTAINABILITY DENGAN MODEL PROBLEM SOLVING TEMA GLOBAL WARMING UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF PESERTA DIDIK THE DEVELOPMENT SCIENCE STUDENT WORKSHEET BASED ON PEDAGOGY FOR SUSTAINABILITY WITH PROBLEM SOLVING MODEL THEME “GLOBAL WARMING” TO IMPROVE CREATIVE THINKING SKILL OF STUDENTS - Rahayu, Duwi Katon; Nurohman, Sabar; Susilowati, Susilowati (Universitas Negeri Yogyakarta, 2017)
Tujuan dari penelitan ini 1) Menghasilkan LKPD IPA berbasis pedagogy for sustainability dengan model problem solving yang layak berdasarkan penilaian validator dan respon peserta didik, 2) Mengetahui karateristik LKPD hasil pengembangan, 3) Mengetahui peningkatan keterampilan berpikir kreatif peserta didik setelah menggunakan LKPD yang dikembangkan. Desain penelitian ini yaitu RD dengan model 4D (Define, Design, Develop, dan Disseminate). Hasil penelitian ini adalah: 1) LKPD IPA berbasis pedagogy for sustainability dengan model problem solving yang layak berdasarkan penilaian validator dan respon peserta didik dengan kategori sangat baik (A), 2) LKPD yang dihasilkan berbasis pedagogy for sustainability dengan empat kompetensi yaitu system thinking and understanding of interconnectedness; longterm, foresighted reasoning, and strategizing; stakeholder engangement and group collaboration; action orientation and change – agent skill, dengan model problem solving yang memiliki sintaks merumuskan masalah, merumuskan hipotesis, mengumpulkan data, menguji hipotesis, menarik kesimpulan dan aplikasi. LKPD ditekankan pada peningkatan keterampilan berpikir kreatif yang meliputi berpikir lancar, luwes, asli dan terperinci, 3) LKPD IPA yang dikembangkan dapat meningkatkan keterampilan berpikir kreatif dibuktikan dengan perolehan gain score sebesar 0,67 katagori sedang.Kata kunci: LKPD IPA, pedagogy for sustainability, problem solving, berpikir kreatif.The aim of this research were 1) to produce a science student worksheet based pedagogy for sustainability with problem solving model reasonable according, 2) to know characteristics of development results of science worksheet, 3) to know improving creative thinking skills after using a science student worksheet that developed. Design of this research was categorized as R D research with 4D model (Define, Design, Develop, and Disseminate). The results of this research of 1) science student worksheet based pedagogy for sustainability with problem solving model theme global warming according to lecture expert, science student and students responses categorized excellent, 2)The characteristic of science student worksheet theme “global warming” are this student worksheet is developed based pedagogy for sustainability with four competence that is system thinking and understanding of interconnectedness; longterm, foresighted reasoning, and strategizing; stakeholder engangement and group collaboration; action orientation and change – agent skill, this student worksheet is using problem solving models with sintaks this is problem formulate, hypothesis formulate, data collect, hypothesis examine, to conclude and to make application, 3) Science student worksheet developed placed emphasis on creative thinking skill. Average the improvement creative thinking skill that was tested is 0,67 and categorized medium.Keywords: science student worksheet, pedagogy for sustainability, problem solving, creative thinking skill